(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2004)
The HIV/AIDS prevention Project for Vietnam aims at reducing transmission of HIV/AIDS and to ensure that HIV prevalence remains below .3 percent - this is a key objective of the Government of Vietnam's National HIV/AIDS Strategy. The project has the following three components: Component 1) will provide sub-grants to 18 provinces (An Giang, Bac Giang, Ben Tre, Cao Bang, Dong Nai, Hau Giang, Khanh Hoa, Kien Giang, Lai Chau, Nam Dinh, Nghe An, Son La, Thai Binh, Thai Nguyen, Thanh Hoa, Tien Giang, Vinh Long, and Yen Bai) and two cities (Hai Phong and Ho Chi Minh City) to support the design and implementation of Annual Provincial Action Plans (PAPS). Component 2) will strengthen capacity at national and provincial levels and promote the development of innovative, effective prevention and treatment approaches and models among vulnerable groups through: (i) demonstration sites that will explore a community-based treatment model to integrate harm reduction with comprehensive HIV treatment and care; (ii) policy studies and research; (iii) knowledge sharing and training; and (iv) other innovations. Component 3) will provide support to the set up and management of the Central Project Management Unit (CPMU) as well as the Provincial Project Management Units (PPMUs) located in the 18 provinces and two cities.
Keywords: HIV infections,Nhiễm HIV,AIDS (Disease),AIDS (Bệnh); Prevention,Phòng ngừa,Prevention,Phòng ngừa